Mentoring Teachers in Developing Industry-Aligned Skill Competency Test Questions - Ismail, Muhamad (Jurnal Dedikasi Pengabdian Pendidikan, 2026)
This community service program aimed to enhance teachers’ competence in developing industry-aligned skill competency test questions for vocational education. The activity was conducted at SMK BMR Pekanbaru on December 12, 2025, in response to limited teacher capacity in designing assessment instruments aligned with industry standards and national competency frameworks. A participatory mentoring approach was implemented through workshops, guided practice, group discussions, and validation sessions. Teachers were assisted in mapping occupational competency standards, developing performance-based test questions, and constructing analytic scoring rubrics relevant to industry needs. The results showed improved teacher understanding of competency-based assessment principles and increased ability to produce customized skill competency test questions supported by clear performance indicators and scoring guidelines. Participants also demonstrated greater confidence in independently developing assessment instruments for future competency examinations. These findings indicate that structured mentoring activities effectively strengthen teachers’ assessment literacy in vocational schools. Aligning competency test instruments with industry requirements enhances the relevance and quality of vocational assessment and helps prepare graduates who meet workforce demands. The program confirms that mentoring-based community service can serve as a sustainable strategy for improving assessment practices and strengthening school–industry alignment in vocational education.